1987
DOI: 10.14430/arctic1818
|View full text |Cite
|
Sign up to set email alerts
|

A Field Evaluation of Selected Beach-Cleaning Techniques

Abstract: ABSTRACT. A series of experiments was conducted to evaluate selected countermeasures for the cleanup of oil on remote beaches. These experiments formed part of the Baffin Island Oil Spill (BIOS) Project, which was conducted at Cape Hatt, N.W.T., between 1980 and 1983. An isolated lagoon was selected with a series of segregated bays that could be used for discrete experiments with control and countermeasure plots. Intertidal control plots were established in 1980 at an exposed site and at a relatively sheltered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…These insights are important for policy and planning aimed at reducing the likelihood of oil spills, providing effective emergency response, and facilitating recovery. Wave exposure Sites exposed to waves will exhibit increased rates of natural degradation of oil over sheltered waterways Owens et al 1987;Carls et al 2001 Temperature and salinity…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These insights are important for policy and planning aimed at reducing the likelihood of oil spills, providing effective emergency response, and facilitating recovery. Wave exposure Sites exposed to waves will exhibit increased rates of natural degradation of oil over sheltered waterways Owens et al 1987;Carls et al 2001 Temperature and salinity…”
Section: Resultsmentioning
confidence: 99%
“…Tides and currents at the time of the spill will influence the direction of the oil's dispersal whereas increased exposure to waves will increase the mechanical mixing energy available for natural oil dispersal and effectiveness of chemical dispersants (Owens et al 1987, Carls et al 2001. Even geographically proximate sites can differ in characteristics that influence an oil spill's impact, such as current flow rates, wave exposure, and substrate, i.e., rocky outcrop vs. sandy beaches.…”
Section: Marine Physical Environmentmentioning
confidence: 99%
“…Knowledge of hydrocarbon biodegradation on high Arctic shorelines to date is largely based on analyses from two large scale field experiments: the Baffin Island Oil Spill (BIOS) in the Canadian High Arctic in 1980 (Sergy and Blackall 1987) and the Svalbard shoreline field trials in Spitsbergen, Norway in 1997 (Guénette et al 2003). During BIOS, a medium gravity crude oil was released in the nearshore environment to evaluate the fate and effects of spilled oil washed onto the shoreline and in the shoreline environment to evaluate various clean-up techniques including burning, mixing, chemical surfactants, solidifying agents and flushing (Owens et al 1987b) and the use of nutrients in the supralittoral shoreline (above high tide) (Eimjhellen et al 1982). Findings from BIOS suggested that despite several weathering processes contributing to oil reduction on shorelines, high Arctic beaches are still vulnerable to long-term oil persistence (Owens et al 1987;Prince et al 2002).…”
Section: Existing Arctic Hydrocarbon Biodegradation and Bioremediatio...mentioning
confidence: 99%
“…However, as well as the waste itself, this action tends to remove sediment, seaweed and small organisms from the sandy soil (Fairweather and Henry, 2003;Ariza et al, 2008). Along with the cleaning, the sandy area is also generally smoothed over after garbage collection to leave it in desirable conditions for the arrival of beach users (Owens et al, 1987;Battisti et al, 2017). Mechanical cleaning has been statistically correlated with the designation of Blue Flag certified beaches (Mir-Gual et al, 2015).…”
Section: Introductionmentioning
confidence: 99%